The Transatlantic Trade Conflict and the German Economy: It Matters how Long It Takes - Sebastian Dullien; Sabine Stephan; Thomas Theobald (Wirtschaftsdienst)
Abstract International trade conflicts continue to simmer in times of the coronavirus crisis. Most recently, in mid-May, the US government tightened export restrictions for suppliers to the Chinese technology company Huawei. Against the background of the dramatic slump in consumer demand for automobiles, US President Donald Trump might revive his protectionist idea of tariffs on cars and car parts from the EU, escalating the transatlantic trade conflict. Economic policy simulations show that such an escalation has the potential to dampen the economic recovery in Germany after the pandemic shock. Fiscal rules limit the ability to counterbalance the macroeconomic impact of a trade war, putting Germany potentially at a relative disadvantage in this conflict.